Tathwīr Mawād at-Taʿlīm li-l-Lughah al-ʿArabiyyah al-Muʿtamadah ʿalā al-Wasāʾiṭ at-Tafāʿuliyyah fī aṣ-Ṣaff as-Sābiʿ bi-Madrasah Mutawassiṭah ad-Dawlah ath-Thānīyah Aceh Tenggara: Developing Arabic Language Teaching Materials Based on Interactive Media for Seventh Grade at the Second State Junior High School, Southeast Aceh - Najmi, Nurun (Critical Review of English-Arabic World Journal, 2025)
الوسائط التفاعلية هي وسائط تجمع بين عدة عناصر مثل النصوص، الرسوم البيانية، الصور، الفيديو، والرسوم المتحركة في مجموعة واحدة تجذب انتباه المتعلمين في عملية التعليم. أجريت هذه الدراسة في المدرسة المتوسطة الحكومية الثانية في أتشيه تنجارا، وكان موضوع البحث طلاب الصف السابع. هدف هذا البحث هو معرفة الإجراءات والنتائج من تطوير الوسائط التفاعلية في تعليم اللغة العربية. نوع هذا البحث هو البحث والتطوير (R&D) باستخدام نموذج التصميم التطويري لبورغ وغال. أظهرت نتائج البحث أن وسائط تعليم اللغة العربية باستخدام الوسائط التفاعلية تمتلك مستوى عالياً من الفاعلية والجاذبية، وذلك من خلال وجود اهتمام ودافعية قوية لدى المتعلمين. كما حصلت هذه الوسائط التعليمية التفاعلية على استجابة إيجابية من المعلمين والمتعلمين، مما جعل عملية التعليم أكثر فاعلية وانضباطاً، وأسهمت في تحفيز الطلاب على تعلم اللغة العربية. أما النتيجة النهائية من عملية التطوير فهي إنتاج وسائط تعليمية للغة العربية على شكل وسائط تفاعلية استوفت مكونات الوسائط التعليمية من خلال عملية التحقق والتجريب. Interactive media are media that combine several elements such as texts, charts, images, videos, and animations into a single set that attracts learners’ attention during the learning process. This study was conducted at the Second State Junior High School in Aceh Tenggara, and the research subjects were seventh-grade students. The aim of this study is to identify the procedures and outcomes of developing interactive media for teaching Arabic. This research is a Research and Development (R&D) study using the Borg and Gall developmental design model. The results of the study indicate that Arabic language teaching media using interactive media possess a high level of effectiveness and attractiveness, as evidenced by strong learner interest and motivation. Additionally, these interactive learning media received positive responses from both teachers and students, making the teaching process more effective and disciplined and contributing to motivating students to learn Arabic. The final outcome of the development process was the production of Arabic language learning media in the form of interactive media that met the components of educational media through a process of validation and testing.